Gereja dan Transformasi Dunia: Hakekat Perayaan Ekaristi Menurut John D. Zizioulas - Subali, Yohanes (Jurnal Orientasi Baru, 2014)
Eucharist is the center of the Orthodox Church. The churchexists because of and in the celebration of the Eucharist. Wherever the Eucharist is, there is the Church.In the Eucharist, the essence of the church is also revealed and celebrated. The church as embodied through the Eucharistis the image of the kingdom of God, since the Eucharist is the anticipation of the future. Through Eucharist, the church moves to its fullness of the kingdom of God. It transforms the world to be sanctified and formed according to the will ofGod. Therefore, the renewal of humanity and the transformation of our world render the logical consequences of the Eucharist and the essence of the church as the image of the kingdom of God.